Two-dimensional thermal finite element model of directed energy deposition: Matching melt pool temperature profile with pyrometer measurement. (September 2020) - Jelinek, Bohumir; Young, William J.; Dantin, Matthew; Furr, William; Doude, Haley; Priddy, Matthew W.
Abstract: An open source two-dimensional (2D) thermal finite element (FE) model of the Directed Energy Deposition (DED) process is developed using the Python-based FEniCS framework. The model incrementally deposits material ahead of the laser focus point according to the geometry of the part. The laser heat energy is supplied by a Gaussian-distributed heat source while the phase change is represented by increased heat capacity around the solidus-liquidus temperature range. Experimental validation of the numerical model is performed by matching with the melt pool temperature measurements taken by a dual wavelength pyrometer during the build process of a box-shaped Ti–6Al–4V part with large geometrical voids. Effects of large geometrical voids on the melt pool shape and maximum melt pool temperature are examined. Both the numerical and experimental data show an increase in the melt pool size and temperature during deposition above large voids. The trailing edge of the melt pool's temperature profile obtained using the developed numerical model closely matches pyrometer measurements.